LUMPY SKIN DISEASE AND ITS EFFECT ON REPRODUCTION AND PRODUCTION IN CATTLE : A LITERATURE REVIEW - Bagas Pria Prasetyo; Lisa Aprilia; Madiyan Sugesti (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Lumpy Skin Disease (LSD) is a emerging infectious disease in cattle caused by the Lumpy Skin Disease Virus (LSDV) from the Capripoxvirus genus. The LSD is a severe infectious disease that has significant clinical and economic impacts on the cattle industry worldwide, and has spread to most Asian countries, especially Southeast Asia. Clinical symptoms include fever, skin nodules (with diameter ranging 0.5–5 cm, emaciation, enlarged lymph nodes, and in some fatal cases, death. The disease is spread by various vectors, such as ticks, mosquitoes, and certain flies. This literature review aimed to summarize scientific knowledge about LSD and its impact on livestock reproduction and production performance. The method used is a systematic literature review of academic databases, such as PubMed, Google Scholar, ResearchGate). The LSD causes significant economic losses due to reduced milk production, skin damage, and weight loss. Reproductive impacts include estrus failure or disorders, repeat breeding, abortion, endometritis, and infertility in bulls. The LSDV virus can persist in the testes, and viral DNA has been found in semen, potentially spreading the disease through artificial insemination. In conclusion, LSD has significant economic impacts due to reduced reproductive and production performance in cattle, threatening the sustainability of livestock business. Enhancements in disease management are needed via improved vaccination strategies and regulated vector control.